Effect of material hybridization on the strength of scarf adhesive joints - Alves, D.L. (2020)
Adhesively-bonded joints have become more efficient due to the improvement of adhesives’ characteristics. On the other hand, with the use of composites in structures it is possible to reduce weight. Due to this, new techniques are being explored, including adhesively-bonding different materials. Nowadays, in many high performance structures, it is necessary to combine composite materials with other light-weighted metals such as aluminium or titanium. This work reports on an experimental and numerical study for hybrid scarf joints between composite and aluminium adherends, and considering different values of the scarf angle (α). The numerical analysis by Finite Elements (FE), using the software Abaqus®, enabled the obtainment of peel (σy) and shear stresses (τxy), which are then used to discuss the strength between different joint configurations. Cohesive zone modelling (CZM) was used to predict the joint strength and the results were compared to the experiments for validation. The joints’ behaviour was highly dependent on α, and CZM were validated for the design process of hybrid scarf joints.